Synthesis and biological activities of some new 4,5-dihydro-1H-1,2,4-triazol-5-ones - (:unkn) unknown (My University, 1996)
The reactions of 3-alkyl(aryl)-4-phenylamino-4,5-dihydro-1H-1,2,4-triazol-5-ones with appropriate alkyl halides via sodio derivatives were studied and the corresponding 1-alkyl-3-alkyl(aryl)-4-phenylamino-4,5-dihydro-1H-1,2,4-traizol-5- ones were synthesized. Next, the new compunds were tested for their in vitro antimicrobial activities.
Keywords: 4,5-dihydro-1H-1,2,4-triazol-5-ones; Biological activity; Synthesis